2018
DOI: 10.1371/journal.pone.0196219
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition versus defense: Why Myzus persicae (green peach aphid) prefers and performs better on young leaves of cabbage

Abstract: Plant leaves of different ages differ in nutrients and toxic metabolites and thus exhibit various resistance levels against insect herbivores. However, little is known about the influence of leaf ontogeny on plant resistance to phloem-feeding insects. In this study, we found that the green peach aphid, Myzus persicae, preferred to settle on young cabbage leaves compared with mature or old leaves, although young leaves contained the highest concentration of glucosinolates. Furthermore, aphids feeding on young l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 37 publications
5
35
0
2
Order By: Relevance
“…These results strongly suggest that aphids have nuanced 'personalities' sensu Schuett et al (2011), with large display of plasticity depending on the embedding environment (Tremmel & Müller, 2013). A possible expression of these aphid personalities may be found in the differential performance on different cabbages that can be driven by the variance in sulphur and glucosinolate production between savoy and red cabbages (Cao et al, 2018). Kanvil et al (2014) showed a similar analogy with pea aphid biotypes reared on various Medicago truncatula genotypes; and this also receives support from our previous experiment with a group of pea aphid clones (Khudr et al, 2017b) showing a large array of contextual performance and behaviour on different cultivars of Vicia faba.…”
Section: Aphidsmentioning
confidence: 80%
See 3 more Smart Citations
“…These results strongly suggest that aphids have nuanced 'personalities' sensu Schuett et al (2011), with large display of plasticity depending on the embedding environment (Tremmel & Müller, 2013). A possible expression of these aphid personalities may be found in the differential performance on different cabbages that can be driven by the variance in sulphur and glucosinolate production between savoy and red cabbages (Cao et al, 2018). Kanvil et al (2014) showed a similar analogy with pea aphid biotypes reared on various Medicago truncatula genotypes; and this also receives support from our previous experiment with a group of pea aphid clones (Khudr et al, 2017b) showing a large array of contextual performance and behaviour on different cultivars of Vicia faba.…”
Section: Aphidsmentioning
confidence: 80%
“…Furthermore, differential age-dependent and line-dependent content of amino acids, sulphur and defensive metabolites (e.g., glucosinolates) may exist between conspecifics (Castro et al ., 2004; Bellostas et al ., 2007) along with distinct leaf morphology (blistered in savoy cabbage but smooth in red cabbage). With a simpler leaf surface/texture, red cabbage phloem is more reachable by aphid stylets than that of savoy; leaf ontogeny also can pose a degree of ecological challenge to aphids as older leaves are less penetrable than younger ones hence the latter are more preferable to colonize (Vickers, 2012; Cao et al ., 2018). Comprehensive information, however, on cultivar by genotype adverse effects of anthocyanins and glucosinolates on aphid performance is thus far lacking ( nota bene ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kutu daun persik dalam penelitian ini banyak ditemukan pada permukaan bawah daun dan pada daun muda, terutama pada pucuk tanaman. Adanya kutu daun persik pada daun muda menyebabkan ekskresi embun jelaga (Cao et al 2018). Menurut Macedo et al (2003) Berdasarkan hasil analisis yang ditunjukkan pada Tabel 5 menunjukkan dapat diketahui bahwa aplikasi ekstrak kulit jeruk bali dan kulit jeruk manis tidak berpengaruh nyata terhadap jumlah daun.…”
Section: Jumlah Daununclassified